Towards a green world: How do green technology innovations affect total-factor carbon productivity - Du, Kerui; Li, Jianglong (Energy policy, 2019)
Alleviating global climate change requires the development and adoption of green technology innovations. Particularly, the sustained economic growth requires green technology innovations in promoting carbon productivity, which is one of the central issues in raising standards of livings without detrimental consequences for global warming. However, the precise impacts of green technology innovations on carbon productivity are still unknown. Here we show that green technology innovations can only take effects for economies with high income, and it is difficult to find significant evidence that green technology innovations positively impact carbon productivity in less developed economies. The findings are quite robust using various alternative model specifications. Furthermore, our results demonstrate the importance of clarifying between development and adoption of green technology innovations. We propose that policy and public intention to raising living standard rather than environment, as well as lacking complementary supporting from other related innovations, represent barriers to adopt green technology innovations in less developed economies. In such countries, we anticipate our paper to attract attention to substantial upgrading of technologies by adopting green technology innovations in their new investments. The findings in this paper also highlight policies for encouraging worldwide green technology cooperation, such as accelerating green technology transfer across economies. •Using a novel data of low-carbon technology stocks to measure green technology innovations.•Providing new evidences on the role of green technology innovations for carbon productivity.•The findings are quite robust using various alternative model specifications.•Two channels are proposed for explaining how income levels matter for the effects.•Highlighting policies for encouraging worldwide green technology cooperation.